Associative and image Framework of the Creolized Text as an Object of the Linguistic Research - Zhukova, Natalia A.; Tonkov, Yevgeniy E.; Komarov, Igor M.; Yaroshchuk, Inna A.; Kosolapova, Natalia A. (Journal of History Culture and Art Research, 2017)
The authors of the article consider the associative and image framework of the creolized text from a position of discursive and pragmatic, intentional analysis which reveals a synergetic complex essence, a role of verbal and non-verbal elements of the creolized text. Our research is based upon a knowledge of linguistics: communicative pragmatics, cognitive linguisticstext linguistics, the theory of a discourse. There are specialized journals devoted to the discursive analysis, e.g. “Text” and “Discourse Processes”. The most known centers of discourse researches are situated in the USA. For example, the California University in Santa Barbara, in Los Angeles, the Oregon University in Eugene, the Georgetown University.